2020
DOI: 10.1515/opag-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Christmas Island rock phosphate and rice straw compost application on soil phosphorus availability and maize (Zea maysL.) growth in a tropical acid soil of Kelantan, Malaysia

Abstract: AbstractPhosphorus (P) fixation is very common in Malaysian acid soils due to the fixation of soluble inorganic P by Al and Fe under acidic soil pH conditions. Farmers tend to perform lots of liming and apply excess amount of P fertilizers in order to saturate the Al and Fe in the soil so that the plants are able to absorb the remaining P. Excessive liming and application of P fertilizers are not only not economical bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Amending acid soils with compost or a mixture of compost and biochar can increase total P, available P, inorganic P fractions (soluble-P, Al-P, Fe-P, redundant soluble P, and Ca-P), and organic P [13]. Similar findings were reported in the work of Sanusi et al [137] and Ch'ng et al [8], where rice straw compost with Christmas Island rock phosphate (CIRP) was found to increase soil-available P in acidic soil. Another study by Mensah and Frimpong [138] showed that the application of compost significantly increased the soil-available P in both the Aiyinase and Cape Coast soils.…”
Section: Compostsupporting
confidence: 77%
See 1 more Smart Citation
“…Amending acid soils with compost or a mixture of compost and biochar can increase total P, available P, inorganic P fractions (soluble-P, Al-P, Fe-P, redundant soluble P, and Ca-P), and organic P [13]. Similar findings were reported in the work of Sanusi et al [137] and Ch'ng et al [8], where rice straw compost with Christmas Island rock phosphate (CIRP) was found to increase soil-available P in acidic soil. Another study by Mensah and Frimpong [138] showed that the application of compost significantly increased the soil-available P in both the Aiyinase and Cape Coast soils.…”
Section: Compostsupporting
confidence: 77%
“…Phosphorus availability is maximised at pH 6.5 for mineral soils and pH 5.5 for organic soils [7]. To reduce P fixation, farmers tend to apply large amounts of P fertiliser and lime to saturate Al and Fe ions and increase the soil pH [8]. However, this practice is uneconomical and environmentally unfriendly because excessive use of P fertilisers causes water pollution, such as in the form of eutrophication.…”
Section: Introductionmentioning
confidence: 99%
“…The reductions in soil exchangeable acidity, Al 3+ , and Fe 2+ for the treatments with charcoal and sago bark ash are related to the increase in soil pH. This finding is consistent with the findings of previous studies which also reported that decrease in exchangeable Al 3+ and Fe 2+ was directly related with the improvement in soil pH [78,82,83]. This was possible because the hydroxyl ions formed from the dissolution of the CaO, MgO, K 2 O, and NaOH in the ash neutralise the protons in the soil solution and those bound on the cation exchange sites in the soil [84].…”
Section: Selected Soil Chemical Properties At Thirty Sixty and Ninety Days Of Incubationsupporting
confidence: 91%
“…Furthermore, commercially viable phosphate rock reserves are diminishing, and some scenarios, though debatable, project their depletion within the next 100 years (Gilbert, 2009). Farmers typically apply significant amounts of P fertilizer and lime to saturate Al and Fe ions and boost soil pH to decrease P fixation (Ch'ng et al, 2020). However, this approach is both inefficient and harmful to the environment, as a higher application of P fertilizers creates water contamination, e.g.…”
Section: Introductionmentioning
confidence: 99%